Alternative splicing produces two transcripts encoding female-biased pheromone subfamily receptors in the navel orangeworm, Amyelois transitella - Garczynski, Stephen F.; Leal, Walter S. (Frontiers in Ecology and Evolution, 2015)
Insect odorant receptors are key sensors of environmental odors and members of the lepidopteran pheromone receptor subfamily are thought to play important roles in mate finding by recognizing sex pheromones. Much research has been done to identify putative pheromone receptors in lepidopteran males, but little attention has been given to female counterparts. In this study, degenerate oligonucleotide primers designed against a conserved amino acid region in the C-terminus of lepidopteran pheromone receptors were used in 3’ RACE reactions to identify candidate pheromone receptors expressed in the antennae of female navel orangeworm. Two near full-length transcripts of 1469 nt and 1302 nt encoding the complete open reading frames for proteins of 446 and 425 amino acids, respectively, were identified. Based on BLAST homology and phylogenetic analyses, the putative proteins encoded by these transcripts are members of the lepidopteran pheromone receptor subfamily. Characterization of these transcripts indicates that they are alternatively spliced products of a single gene. Tissue expression studies indicate that the transcripts are female-biased with detection mainly in female antennae. To the best of our knowledge, these transcripts represent the first detection of alternatively spliced female-biased members of the lepidopteran pheromone receptor subfamily.